(untitled) (Journal of National Institute of Neurosciences Bangladesh, 2023)
Background: Tension-type headache is frequently reported by the patients. Objective: The purpose of the present study was to see the status of thyroid hormones among chronic tension type headache patients. Methodology: This study was conducted in the Department of Neurology at Dhaka Medical College, Dhaka, Bangladesh. The study subjects consisted of patients presented with primary headache disorders. Result: Among the patients 21.0% had chronic sub-type of TTH. Out of 42 chronic tension-type headache patients 12 had subclinical and another 12 had overt hypothyroidism. Statistically significant difference was seen among different sub-types of headache in relation to thyroid status. Conclusion: Hypothyroidism is found to be a co morbidity or precipitating factors to be development of chronic type of tension-type headache. Journal of National Institute of Neurosciences Bangladesh, July 2022;8(2):189-192